Cross-field potential hill arisen eccentrically in toroidal electron cyclotron resonance plasmas in the Low Aspect ratio Torus Experiment device to regulate electron and ion flows from source to boundary. (18th June 2015) - Kuroda, Kengoh; Wada, Manato; Uchida, Masaki; Tanaka, Hitoshi; Maekawa, Takashi
Abstract: We have investigated the electron and ion flows in toroidal electron cyclotron resonance (ECR) plasmas maintained by a 2.45 GHz microwave power around 1 kW under a simple toroidal field in the low aspect ratio torus experiment (LATE) device. We have found that a vertically uniform ridge of electron pressure that also constitutes the source belt of electron impact ionization is formed along just lower field side of the ECR layer and a cross-field potential hill ( 30 V while 10 eV), eccentrically shifted toward the corner formed by the top panel and the ECR layer, arises. Combination of the hill-driven drift and the vertical drift due to the field gradient and curvature, being referred to as vacuum toroidal field (VTF) drift, realizes steady flows of electrons and ions from the source to the boundary. In particular, the ions, of which VTF drift velocity is much slower than the electron VTF drift velocity near the source belt, are carried by the drift around the hill to the vicinity of the top panel, where the ion VTF drift is enhanced on the steep down slope of potential toward the top panel. On the other hand the electron temperature strongly decreases in this area. Thus the carrier of VTF drift current is replaced from the electrons to the ions before the top panel, enabling the current circulation through the top and bottom panels and the vessel (electrons mainly to the bottom and ions mainly to the top) that keeps the charge neutrality very high. A few percent of electrons from the source turn around the hill by 360 degree and reentry the source belt from the high field side as seed electrons for the impact ionization, keeping the discharge stable.